Circular bioeconomy - current developments and future outlook - Pandey, Ashok; Tyagi, R. D.; Varjani, Sunita (Amsterdam, Netherlands : Elsevier, 2021)
'Biomass, Biofuels, Biochemical: Circular Bioeconomy: Current Developments and Future Outlook presents the views of experienced academicians and researchers working in the area of the circular bioeconomy. This book presents an assortment of Resource recovery, Waste Biorefineries, Bio-electrochemical systems, Biopolymers and Green solvents, Bio-adsorbents, and Technology transfer topics. Environmental engineers, biotechnologists, science graduates, chemical engineers, industrial experts and policymakers working in these areas will find the information on the circular economy and its important part in developing low carbon and resource-productive economies very informative. Methodologies and beneficial strategic approaches to address the usage of wastes from agriculture, co-products, and by-products are also discussed'--
Includes bibilographical references and index.
Keywords: Biomass energy